IMPLEMANTASI DIGITAL MARKETING SEBAGAI STRATEGI PROMOSI PRODUK KONVEKSI HOME INDUSTRI - Kasmi, Kasmi; Prayoga, Raihan Nabih (Jurnal Signaling, 2023)
Digital marketing is a very popular strategy and is used by almost all marketers throughout the world. This is the influence of the internet and the increasingly developing world of technology, making the internet a very potential market. Digital marketing has many advantages over traditional marketing. These benefits include easy access to a wider target market, lower costs and two-way communication with potential customers. So it is not easy to build a successful digital marketing advertising business. However, when you start with digital marketing, things get much better. The method used in this research uses the waterfall model development method, the reason is because the work model is linear which minimizes errors, and the production is structured and the direction is clear. Identifying problems with the sales system and producing an information system that can make it easier for the owner to manage his business and attract customers' interest in purchasing/ordering the products being sold. The result of this research is a sales promotion information system that can make it easier for owners to manage their business and can improve the quality of their service and increase the number of customers through a sales promotion system and make it easier for buyers to make purchases and order products for sale.